Accessibility in People with Disabilities in Primary Healthcare Centers: A Dimension of the Quality of Care - Rojas-Pavez, J; Coss-Mandiola, J; Vanegas-Lopez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The purpose of this research is to evaluate universal accessibility in primary healthcare (PHC) centers in the Atacama region, Chile, through an analytical cross-sectional study with a quality approach, which uses the external audit model with the application of a dichotomous comparison guideline, evaluating levels of compliance with four dimensions of universal accessibility described in the literature: participation, information, accessibility chain and architectural aspects. This was carried out in 18 PHC, and set as Lower Control Limit (LCL) of 70% to compare levels of compliance, and a hierarchical model and k-mean analysis were applied. Results: Very low compliance averages were obtained, 37.7% participation, 4% information, 44.4% access chain, and 63.9% architectural aspects, indicating a critical situation. Moreover, the cluster comparison allowed to observe that a group of healthcare centers complies more than other groups, which requires more attention. Conclusions: The low level of accessibility for people with disabilities may be associated with various factors that require further monitoring and analysis. However, low levels of accessibility require changing the way of relating to this vulnerable group of the population, and considering including them in the design and reasonable adjustments made in PHC centers. The findings from this research open the possibility for future research that increases understanding of how to reduce barriers in a such wide variety of forms of disability. © 2022 by the authors.